Adventism and Mediatization of Fake News Becoming a Church - Bratosin, Ştefan (Religions, 2024)
This article explores the becoming-church of fake news against the background of the rise of the mediatization of faith and religious beliefs through classic media supports, such as newspapers, magazines, and journals, between 1840 and 1863 in the United States. The analysis focuses on the expression of Seventh-day Adventist Church beliefs in the Adventist press before 1863. The observation of this corpus follows the construction of the “narrative” of fake news from the story propagated by William Miller. The aim is to understand how the Seventh-day Adventist Church was created in the media from the fake news of William Miller. The article shows that the mediatization of William Miller’s fake news made the Seventh-day Adventist Church appear as the embodiment of an agnostic movement, as the material trace of a cultural expression of romanticism, but also as a spiritual organization, with a social and auxiliary political vocation.